2020
DOI: 10.1093/mnras/staa1996
|View full text |Cite
|
Sign up to set email alerts
|

Long-term study of extreme giant pulses from PSR B0950+08 with AARTFAAC

Abstract: We report on the detection of extreme giant pulses (GPs) from one of the oldest-known pulsars, the highly variable PSR B0950+08, with the Amsterdam-ASTRON Radio Transient Facility And Analysis Centre (AARTFAAC), a parallel transient detection instrument operating as a subsystem of the LOw Frequency ARray (LOFAR). During processing of our Northern Hemisphere survey for low-frequency radio transients, a sample of 275 pulses with fluences ranging from 42 to 177 kJy ms were detected in one-second snapshot images. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
49
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(62 citation statements)
references
References 44 publications
11
49
2
Order By: Relevance
“…This value of corresponds to approximately 360 average pulses (APs) assuming mean flux of 2.37 Jy at 150 MHz (Lorimer et al 1995) and pulsar period s according to the ATNF pulsar catalogue (Manchester et al 2005). This is very similar to the distributions of GP fluences previously reported by Kuiack et al (2020c) and shown in Figure 6 in their paper, where their fitted power law indexes were and at frequency 58.3 MHz and and at 61.8 MHz. In their work, the ‘break fluence’ values were 45 AP fluences at 58.3 MHz and 88 AP fluences at 61.8 MHz.…”
Section: Preliminary Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…This value of corresponds to approximately 360 average pulses (APs) assuming mean flux of 2.37 Jy at 150 MHz (Lorimer et al 1995) and pulsar period s according to the ATNF pulsar catalogue (Manchester et al 2005). This is very similar to the distributions of GP fluences previously reported by Kuiack et al (2020c) and shown in Figure 6 in their paper, where their fitted power law indexes were and at frequency 58.3 MHz and and at 61.8 MHz. In their work, the ‘break fluence’ values were 45 AP fluences at 58.3 MHz and 88 AP fluences at 61.8 MHz.…”
Section: Preliminary Resultssupporting
confidence: 91%
“…The relative rarity of occurrence (3 nights out 24 spread over nearly 6 months) further supports such a conjecture. A similar possibility was also suggested by the recent work of Kuiack et al (2020c).…”
Section: Preliminary Resultssupporting
confidence: 85%
See 3 more Smart Citations